2015
DOI: 10.1126/science.aaa5542
|View full text |Cite
|
Sign up to set email alerts
|

Engram cells retain memory under retrograde amnesia

Abstract: Memory consolidation is the process by which a newly formed and unstable memory transforms into a stable long-term memory. It is unknown whether the process of memory consolidation occurs exclusively by the stabilization of memory engrams. By employing learning-dependent cell labeling, we identified an increase of synaptic strength and dendritic spine density specifically in consolidated memory engram cells. While these properties are lacking in the engram cells under protein synthesis inhibitor-induced amnesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

63
627
3
5

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 604 publications
(698 citation statements)
references
References 41 publications
63
627
3
5
Order By: Relevance
“…The retrieval deficit in early AD models is similar to memory deficits observed in amnesia induced by impairing memory consolidation via protein synthesis inhibitors 14 . The underlying mechanism of memory failure in early AD patients may not necessarily parallel the molecular and circuit impairments observed in mouse models of early AD.…”
Section: Main Textsupporting
confidence: 56%
See 4 more Smart Citations
“…The retrieval deficit in early AD models is similar to memory deficits observed in amnesia induced by impairing memory consolidation via protein synthesis inhibitors 14 . The underlying mechanism of memory failure in early AD patients may not necessarily parallel the molecular and circuit impairments observed in mouse models of early AD.…”
Section: Main Textsupporting
confidence: 56%
“…In addition, our recent study of protein synthesis inhibitor-induced amnesia found reduced engram-cell specific dendritic spine density 14 . We detected an age-dependent (Extended Data Fig.…”
Section: Main Textmentioning
confidence: 99%
See 3 more Smart Citations